Diurnal variation in aggressiveness - behavioural analysis in the yellow-headed gecko Gonatodes albogularis (2015)
Several physiologieal and behavioural proeesses of vertebrates such as body temperature and locomotor activity are controlled by intenal clocks of approximately 24 hours, eommonly referred as circadian rhythms The role of circadian rhythms on aggressiveness has received special attention in order to understand the physiological and environmental factors underpinning social interactions. In vertebrates, testosterone is positively assoeiated with aggressive and dominant behaviour. Furthermore, as testosterone takes place in the development of sexual traits, it has been correlated with male ecological success. Most studies reporting diurnal variation in aggressive behaviour disregard the ecological implications of the variation in behaviour. Using behavioural, morphological and physiological approaches we evaluated diurnal variation in aggressive behaviour in the yellow-headed gecko Gonatodes albogularis under laboratory conditions